The Revised Statutes of the State of Florida 782-83 (W.A. Blount et al. eds., 1892) - (:unkn) unknown (My University, 1868)
1868 Fla. Rev. Stat., tit. 2, art. 5, § 2425: Prohibited the manufacture or sale of slungshots or metallic knuckles. Punishable by imprisonment for up to 6 months or a fine up to $100.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - NON-GUN ARMS